Incremental validity of assessment centre exercise ratings over and above general mental ability and personality traits in predicting financial intermediaries regulatory examination success and sales performance - Hesqua, Rene (Organisational Psychology, 2019)
The present study explored the optimal selection of financial intermediaries in the South African insurance services industry. We examined the potential predictive value of competency-based selection assessment centre (AC) exercises, when used in combination with other traditional measures (e.g., interviews, work style interest questionnaire, general mental ability and personality traits) in an incremental validity study. Moreover, the study expanded the criterion domain by considering prediction models for multiple outcome measures, including examination success of intermediaries and their objective sales performance. The sample consisted of 425 intermediaries in the middle and affluent market segments in South Africa. We reduced the large number of potential predictors through principle component analysis and subsequently conducted hierarchical regression analysis. Results showed that when the independent variables were restricted to correlating predictors as part of the further analysis, assessment centre exercises, especially the role-play, had a significant incremental effect (ΔR²=.07, <.05) over general mental ability (GMA) in predicting examination marks. Personality traits (e.g., emotional stability) and assessment centre ratings contributed significantly to examination success. To predict sales performance, the personality measure incremented GMA and AC exercises (ΔR²=.08, p < .05). GMA and AC exercises did not contribute in predicting sales performance and could not add incremental validity (ΔR² = .01, p > .05). The work style questionnaire (ΔR² = .03, p < .05) and interview (ΔR² = .012, p < .05) selection measures incremented both AC exercises and personality traits in predicting sales performance. The study contributes to our understanding of predictor combinations when academic and objective performance criteria are considered in a specific applied setting (e.g., a niche industry). The practical implications of the findings are that the validity of the assessment centre exercises together with other measures could be enhanced since it can predict different aspects of performance.